MORFOTEKTONIK DAN REAKTIVITAS SESAR SUMATERA DI PADANGPANJANG, SUMATERA BARAT - Poedjoprajitno, S. (Pusat Survei Geologi, 2007)
Studies on tectonic morphology in the Sumatera fault zone at Padangpanjang segment by using lineament analysis on transect and landsat image have recoqnized some tectonic landform features. These features are among others,curvature of Kubu ridge line, eroded faultscarp, alignment of Kayutanduk sagpond, Kotobaru sagpond, Talago sagpond, Tanang River, and Airanget and Gadis River fault valley at Batipuh village and surrounding area. Keywords : tectonic landform, morphostructure, morphotectonic